Studi Pengaruh Konsentrasi Katalis ZnO untuk Degradasi Limbah Palm Oil Mill Effluent (POME) Menggunakan Teknologi Fotokatalitik - Wahyudi, Farizky; Wibawa Hendra Saputera; Dwiwahju Sasongko; Hary Devianto (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2023)
Indonesia is among the world’s largest palm oil market countries leading to significant growth in the domestic palm oil industry. However, the increase in palm oil trading has also led to a rise in the production of waste known as Palm Oil Mill Effluent (POME). Currently, the majority of factories use open ponds for POME processing, but this method is considered ineffective for treating POME. To address this issue, researchers are exploring photocatalytic technology, which utilizes light energy (UV, visible, sunlight) to produce radical compounds that act as oxidizing agents for POME degradation. In this study, ZnO was employed as a catalyst. The XRD and UV-vis DRS characterizations confirmed that ZnO had a hexagonal wurtzite crystal structure with a band gap energy of 3,22 eV. The photocatalytic activity test results revealed that using 0.5 g/L ZnO catalyst proved to be efficient in degrading organic content in POME. The percentage of chemical oxygen demand (COD) degradation reached 22.85%, color degradation reached 48.53% and the reaction rate kinetics constant of COD degradation was at 2.6´10-3 min-1.